Reinstating plasticity and memory in a tauopathy mouse model with an acetyltransferase activator - Snehajyoti Chatterjee; Raphaelle Cassel; Anne Schneider‐Anthony; Karine Merienne; Brigitte Cosquer; Laura Tzeplaeff; Sarmistha Halder Sinha; Manoj Kumar; Piyush Chaturbedy; Muthusamy Eswaramoorthy; Stéphanie Le Gras; Céline Keime; et al. (EMBO Molecular Medicine)
Abstract Chromatin acetylation, a critical regulator of synaptic plasticity and memory processes, is thought to be altered in neurodegenerative diseases. Here, we demonstrate that spatial memory and plasticity (LTD, dendritic spine formation) deficits can be restored in a mouse model of tauopathy following treatment with CSP‐TTK21, a small‐molecule activator of CBP/p300 histone acetyltransferases (HAT). At the transcriptional level, CSP‐TTK21 re‐established half of the hippocampal transcriptome in learning mice, likely through increased expression of neuronal activity genes and memory enhancers. At the epigenomic level, the hippocampus of tauopathic mice showed a significant decrease in H2B but not H3K27 acetylation levels, both marks co‐localizing at TSS and CBP enhancers. Importantly, CSP‐TTK21 treatment increased H2B acetylation levels at decreased peaks, CBP enhancers, and TSS, including genes associated with plasticity and neuronal functions, overall providing a 95% rescue of the H2B acetylome in tauopathic mice. This study is the first to provide in vivo proof‐of‐concept evidence that CBP/p300 HAT activation efficiently reverses epigenetic, transcriptional, synaptic plasticity, and behavioral deficits associated with Alzheimer's disease lesions in mice.